Characterization of the SUF FeS cluster synthesis machinery in the amitochondriate eukaryote Monocercomonoides exilis - Peña-Diaz, Priscila; Braymer, Joseph J; Vacek, Vojtěch; Zelená, Marie; Lometto, Stefano; Mais, Christopher-Nils; Hrdý, Ivan; Treitli, Sebastian C; Hochberg, Georg K A; Py, Béatrice; Lill, Roland; Hampl, Vladimír (Current biology, 2024)
Monocercomonoides exilis is the first known amitochondriate eukaryote. Loss of mitochondria in M. exilis ocurred after the replacement of the essential mitochondrial iron-sulfur cluster (ISC) assembly machinery by a unique, bacteria-derived, cytosolic SUF system. It has been hypothesized that the MeSuf pathway, in cooperation with proteins of the cytosolic iron-sulfur protein assembly (CIA) system, is responsible for the biogenesis of FeS clusters in M. exilis, yet biochemical evidence is pending. Here, we address the M. exilis MeSuf system and show that SUF genes, individually or in tandem, support the loading of iron-sulfur (FeS) clusters into the reporter protein IscR in Escherichia coli. The Suf proteins MeSufB, MeSufC, and MeSufDSU interact in vivo with one another and with Suf proteins of E. coli. In vitro, the M. exilis Suf proteins form large complexes of varying composition and hence may function as a dynamic biosynthetic system in the protist. The putative FeS cluster scaffold MeSufB-MeSufC (MeSufBC) forms multiple oligomeric complexes, some of which bind FeS clusters and form selectively only in the presence of adenosine nucleotides. The multi-domain fusion protein MeSufDSU binds a PLP cofactor and can form higher-order complexes with MeSufB and MeSufC. Our work demonstrates the biochemical property of M. exilis Suf proteins to act as a functional FeS cluster assembly system and provides insights into the molecular mechanism of this unique eukaryotic SUF system.
Keywords: functional protistology; amitochondriate; Protozoan Proteins; proteiny obsahující železo a síru; FeS clusters; protozoální proteiny; Escherichia coli; protist; SUF system; Iron-Sulfur Proteins